XR for Shared Situation Awareness: Design Thinking and Industrial Application - Karjalainen, Jaakko (2025)
In automation-intensive industrial environments, maintaining shared situation awareness across mixed fleets of human and machine agents presents a complex design challenge. Effective solutions must be cognitively grounded, role-sensi- tive, and aligned with socio-technical constraints. This thesis addresses this chal- lenge by developing a design thinking framework through a design science re- search process to guide the development of extended reality applications for sup- porting situation awareness. The framework integrates theories of individual, shared, and distributed situation awareness with a life-based design approach to ensure alignment with users’ cognitive capacities, roles, and operational contexts. Empirical material from the intralogistics domain informed the development of the framework by providing insights into challenges related to situation aware- ness and contextual constraints in mixed fleet operations. These findings were translated, through the structuring logic of life-based design, into concept-level interventions and narrative scenarios that illustrate how extended reality can structure and deliver situation-relevant information in complex operational con- texts. The resulting framework offers structured guidance for designing solutions that are cognitively appropriate and contextually compatible for supporting sit- uation awareness in human–technology collaboration. While developed in the context of intralogistics, the framework is intended to be applicable to other au- tomation-intensive domains where coordination between human and machine agents is critical. The study provides a theoretically grounded and empirically informed foundation for both future research and the design of extended reality– based support systems in complex socio-technical environments.